Influence of Migration Processes on the Demographic Development of the North of Buryatia in 1970s-1980s - O. A. Ubeeva (Научный диалог, 2019)
The history of the demographic development of the population of the northern regions of Buryatia in the late Soviet period represents one of the poorly studied topics in Russian historiography. The presented work focuses on migration processes and their impact on the population of the north of Buryatia during the construction of the Baikal-Amur Mainline. It is noted that the state set the task of increasing the survival rate and securing migrants in the territories that were in the zone of influence of the “construction of the century”. It is shown that the dynamics of migration directly depended on the activity of migration flows, due to which there was an increase in population density in the construction zone of the highway. When considering the influence of migration processes on demographic development, three periods are identified in the work. It is indicated that the second half of the 1970s was characterized by an increase in the population due to active labor migration, while the inflow of men and women of working age was reflected in the indicators of the natural movement of the population. However, the natural growth was insignificant and did not have a qualitative impact on the demographic picture of the northern regions of the republic. The authors show that in the first half of the 1980s there was an equalization of the intensity of migration processes with a slight outflow of the population; since 1985, statistics has shown an active reverse outflow of migrants with ongoing labor migration to the northern regions of the republic.